Spatial and Temporal Variability of Sea Surface Temperature in Eastern Marginal Seas of China - Renhao Wu; Jianmin Lin; Bo Li (Advances in Meteorology)
Spatial mean value evolution, long-term mean pattern, and seasonal as well as interannual variability of sea surface temperature (SST) in Eastern Marginal Seas of China (EMSC) are reanalyzed based on thirty years’ NOAA optimum interpolation (OI) 1/4 degrees’ daily SST data. Temporal evolution of the spatial mean value shows a very marked annual cycle and a weak warming tendency (0.03437°C/year). Spatial distribution of the long-term mean value shows some more fine spatial structure of SST compared to previous studies. Over 90% of the temporal variability can be explained by the annual harmonic whose amplitude is one order larger than that of the semiannual harmonic. In addition, the annual harmonic amplitude distribution is consistent with that of the value of standard deviation. In order to investigate the interannual variation of SST, the EMSC SST interannual index was constructed. Based on wavelet analysis, a significant peak around 3.3 years was found in the EMSC SST interannual index. Further analysis demonstrated that the interannual variability of SST is linked with El Niño-Southern Oscillation (ENSO) teleconnection, through which anomalous surface heat flux warms or cools the EMSC during El Niño or La Niña events.